Autoavaliação do estado de saúde e analfabetismo como preditores de morte em uma coorte brasileira - Inuzuka, Sayuri (2018)
Background: Identify individuals with reduced life expectancy is a priority in public health policies and a central issue in decision making in clinical care. There are few cohort studies in developing countries addressing self-rated health status and illiteracy as death predictors. Objectives: Determine if self-rated health status and illiteracy are predictors of mortality from cardiovascular disease. Methods: A prospective population study was conducted in a small Brazilian city aiming to determine if self-rated health status and illiteracy were predictors of cardiovascular disease and non-cardiovascular mortality. The cohort was established in 2002 (phase 1) with a representative sample of adults living in the city, and the same individuals were re-assessed in 2015 (phase 2). Data on sociodemographic, anthropometric, lifestyle variables, previous CVD, and SRH were collected in both phases. Multivariable logistic regression models were designed to identify variables from phase 1 that predicted death (all causes, CVD and non-CVD) in phase 2. Results: From the original sample of 1167 subjects included in the phase 1, 101 were excluded from this study. The final sample size was 1066 individuals. Mean age was 42.7±13.8y in phase 1 and 56.1±13.8y in phase 2. From a total of 1066 individuals included, 95 (9%) died of non-CVD causes and 53 (5%) died from CVD causes. Very good/excellent SRH in 2002, was found in 57% of those alive in 2015, compared to 31.1% in the death group (p<0.001). Oppositely, fair/poor SRH in 2002 was more frequent (18.9%) in those dead in 2015 when compared to those living (18.9% x 7.7% - p<0.001). Illiteracy, in 2002, was more frequent in individuals deceased in 2015 when compared to those living (35.1% x 11% - p<0.001). SRH was predictor of CVD death (OR 0.68; 95%CI 0.46 – 0.99; p= 0.049) and all causes of death (OR 0.77; 95%CI 0.60 – 0.99; p=0.049) after the follow-up time while illiteracy predicted Non-CVD death (OR 1.79; 95%CI 1.06 – 3.04; p=0.030). Conclusion: Worse SRH status was predictor of CVD death and all causes of death but not Non-CVD death, and illiteracy predicted Non-CVD death but not CVD death or death from all causes after 13 years of follow-up in a Brazilian cohort.